Atividade mediatizadora, juventude e a apropriação política dos espaços por meio da heterogeneidade criadora - Pavani, Marcos Roberto (Universidade Federal de São Carlos, 2021)
This doctoral research addresses the youth actions of appropriation of social spaces, such as: the virtual space, the school and the geographic space. The research question that guided and supported the study was: how did digital media activities of communication interfere in youth mobilizations in 2015 and 2016, in learning, in political appropriations of social spaces and in the transformation of the material conditions of the geographic space in question. Therefore, the objective was to analyze the contribution of digital communication tools, formal and non-formal, to actions of resistance and youth political appropriations of spaces virtual, school and geographic, as well as its consequences and its potentialities related to the creative heterogeneity of citizen conditions. This thesis was based on the theoretical-methodological frameworks of Critical Geography and Historical-Cultural Theory, based on the studies of Milton Santos, David Harvey, Boaventura de S. Santos, Lev. S. Vigotsky, Arthur V. Petrovski, among others, which effectively contribute to research and understanding forms of development of social practices and human learning. The methodological approach was based on historical-dialectical materialism, in case studies related to virtual space, school and geographic space, based on documentary and field research (in person and remote). The instruments used were: semi-structured interviews, virtual questionnaires (google forms), document analysis (newspapers, videos, pedagogical political project) and observation. The participants were: a group of young students from public schools completing high school, who participated directly in the actions of secondary occupations in 2015 and 2016, in the states of Goiás, Minas Gerais, São Paulo and Paraná, professionals working in two educational institutions public from São Paulo, a digital influencer of the virtual platform You Tube, a young activist from the community of Heliópolis - São Paulo – and a social educator. The analysis of the results was carried out through the following data analysis guidelines: geographic space, mediated activity, digital tools, political appropriation of social spaces by youth and heterogeneity that created citizenship, which originated from the crossing of data from the various instruments, from the question and research objectives, as well as theoretical references. The results corroborate the importance of formal and non-formal educational activities related to social situations, in order to enhance different learning of young people, as well as the development of human skills related to overcoming and recreating existing material conditions, highlighting mediation fundamental in these educational practices, the use of digital communication tools that re-signified and expanded such practices. In addition, the results also reinforce what is emphasized by Critical Geography and Historical-Cultural Theory research, that is, that the transformation of socio-spatial realities is directly conditioned to the development of the population's creative abilities, which, through their mobilizations and collective actions, is capable of elaborating new paradigms, such as the heterogeneity creator of your citizenship.
Mediating activity, youth and the political appropriation of spaces through creative heterogeneity
Actividad mediadora, juventud y apropiación política de los espacios a través de la heterogeneidad creadora
Keywords: Atividade mediatizada; Ferramentas digitais de comunicação; Apropriação política dos espaços; Heterogeneidade criadora; Mediated activity; Digital communication tools; Political appropriation of spaces; Creative heterogeneity; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM